Microbiological quality of human consumption water in a school in Maringa-PR - Ueda Yamaguchi, Mirian; Ranieri Cortez, Lúcia Elaine; Camargo Ottoni, Lilian Cristina; Oyama, Jully (O Mundo da Saúde, 2013)
Contaminated water associated with poor sanitation kills about 1.6 million people worldwide annually. Lack of potability in water is not always perceptible to the sight or smell, requiring laboratory analysis to detect it. Because of that it is important to control microbiologically water since it is a vehicle of transmission of bacteria such as total and fecal coliforms, protozoa, viruses and fungi that cause numerous humans diseases. These microorganisms cause diarrhea, dysentery, hepatitis, cholera, among other serious illnesses. This research aimed at examining the presence of total and fecal coliforms in samples from bottled mineral water and treated water. In the present study 50 sites of drinking water were selected, all located in an educational institution in Maringá-PR. 13 of the collected samples were from water drinker dispensers with bottled natural mineral water and 37 samples were from water dispensers with water treated in their own institution. The methodology used for detecting coliforms was the method of Multiple Tube Fermentation. The result of this study revealed – through microbiological analysis – that the samples of treated water were fit for human consumption. However, 15.38% of the analyzed mineral water samples were contaminated with total coliforms. These results showed that water treated with chlorine showed better microbiological quality when compared to bottled natural mineral water.